A pragmatic health centre-based evaluation comparing the effectiveness of a PCV13 schedule change from 3+0 to 2+1 in a high pneumococcal carriage and disease burden setting in Malawi: a study protocol. Issue 6 (17th June 2021) - Swarthout, Todd D; Ibarz-Pavon, Ana; Kawalazira, Gift; Sinjani, George; Chirombo, James; Gori, Andrea; Chalusa, Peter; Bonomali, Farouck; Nyirenda, Roseline; Bulla, Edwin; Brown, Comfort; Msefula, Jacquline; et al.
Abstract : Introduction: Streptococcus pneumoniae (the pneumococcus) is commonly carried as a commensal bacterium in the nasopharynx but can cause life-threatening disease. Transmission occurs by human respiratory droplets and interruption of this process provides herd immunity. A 2017 WHO Consultation on Optimisation of pneumococcal conjugate vaccines (PCV) Impact highlighted a substantial research gap in investigating why the impact of PCV vaccines in low-income countries has been lower than expected. Malawi introduced the 13-valent PCV (PCV13) into the national Expanded Programme of Immunisations in 2011, using a 3+0 (3 primary +0 booster doses) schedule. With evidence of greater impact of a 2+1 (2 primary +1 booster dose) schedule in other settings, including South Africa, Malawi's National Immunisations Technical Advisory Group is seeking evidence of adequate superiority of a 2+1 schedule to inform vaccine policy. Methods: A pragmatic health centre-based evaluation comparing impact of a PCV13 schedule change from 3+0 to 2+1 in Blantyre district, Malawi. Twenty government health centres will be randomly selected, with ten implementing a 2+1 and 10 to continue with the 3+0 schedule. Health centres implementing 3+0 will serve as the direct comparator in evaluating 2+1 providing superior direct and indirect protection against pneumococcal carriage. Pneumococcal carriage surveys will evaluate carriage prevalence among children 15–24 months, randomised at household level, and schoolgoers 5–10 years of age, randomly selected from school registers. Carriage surveys will be conducted 18 and 33 months following 2+1 implementation. Analysis: The primary endpoint is powered to detect an effect size of 50% reduction in vaccine serotype (VT) carriage among vaccinated children 15–24 months old, expecting a 14% and 7% VT carriage prevalence in the 3+0 and 2+1 arms, respectively. Ethics and dissemination: The study has been approved by the Malawi College of Medicine Research Ethics Committee (COMREC; Ref: P05.19.2680), the University College London Research Ethics Committee (Ref: 8603.002) and the University of Liverpool Research Ethics Committee (Ref: 5439). The results from this study will be actively disseminated through manuscript publications and conference presentations. Trial registration number: NCT04078997 .